Addressing challenges in production of cellulases for biomass hydrolysis: Targeted interventions into the genetics of cellulase producing fungi. (June 2021) - Sukumaran, Rajeev K.; Christopher, Meera; Kooloth-Valappil, Prajeesh; Sreeja-Raju, AthiraRaj; Mathew, Reshma M.; Sankar, Meena; Puthiyamadam, Anoop; Adarsh, Velayudhanpillai-Prasannakumari; Aswathi, Aswathi; Rebinro, Valan; Abraham, Amith; Pandey, Ashok
Highlights: Enzymes acting on lignocellulose are introduced in context of biomass hydrolysis. Understanding gene regulation in fungi is the key to enhancing enzyme production. Modulation of fungal gene regulation for improved cellulase production described. Control of transcription factors, signal transduction and secretion are critical. Abstract: Lignocellulosic materials are the favoured feedstock for biorefineries due to their abundant availability and non-completion with food. Biobased technologies for refining these materials are limited mainly by the cost of biomass hydrolyzing enzymes, typically sourced from filamentous fungi. Therefore, considerable efforts have been directed at improving the quantity and quality of secreted lignocellulose degrading enzymes from fungi in order to attain overall economic viability. Process improvements and media engineering probably have reached their thresholds and further production enhancements require modifying the fungal metabolism to improve production and secretion of these enzymes. This review focusses on the types and mechanisms of action of known fungal biomass degrading enzymes, our current understanding of the genetic control exerted on their expression, and possible routes for intervention, especially on modulating catabolite repression, transcriptional regulators, signal transduction, secretion pathways etc., in order to improve enzyme productivity, activity and stability.